1996
DOI: 10.1002/ana.410400614
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical phenotype of two missense mutations in the presenilin I gene in Japanese patients

Abstract: We report the clinical and neuropathologic phenotypes associated with two different missense mutations in the presenilin 1 (PS-1) gene in Japanese patients with early-onset familial Alzheimer's disease (FAD). In the AM/JPN1 pedigree a missense mutation (C-->T) was found at nucleotide 1102, which is predicted to cause an alanine-to-valine missense substitution at codon 260. In this family, the disease had a mean age of onset of 40.3 years and an indolent course (range, 8-19 years). Neuropathologic studies in 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…Interestingly, neuropathological examination in a patient with PS1 G183V revealed tauopathy in the form of Pick bodies and complete absence of amyloid plaque pathology [57]. Consistent with the idea that PS mutations can produce Pick bodies [57], co-existent AD and Pick body pathology was observed in patients with PS1 M146L and A260V mutations [58,59].…”
Section: Glossarymentioning
confidence: 52%
“…Interestingly, neuropathological examination in a patient with PS1 G183V revealed tauopathy in the form of Pick bodies and complete absence of amyloid plaque pathology [57]. Consistent with the idea that PS mutations can produce Pick bodies [57], co-existent AD and Pick body pathology was observed in patients with PS1 M146L and A260V mutations [58,59].…”
Section: Glossarymentioning
confidence: 52%
“…The KG family mutation (P264L) has been observed in two other families (Campion et al, 1995;Wasco et al, 1995) and in each case, the onset ages cluster tightly around 45 years. The AM family mutation (A260V) also has been observed in another Japanese family ; cosegregation of this mutation with AD in this family has been described elsewhere (Ikeda et al, 1996). The SNW family mutation C410Y (see also Sherrington et al, 1995) has been observed in two other FAD families (Campion et al, 1995;Sherrington et al, 1995) with onset ages ranging from 40-60 years.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical features of the L, V, AM, and SNW families have been described previously (Cook et al, 1979;Bird et al, 1989;Lampe et al, 1994;Ikeda et al, 1996. the HRX-III family, a nonconservative amino acid change (A426P) is found in both affected subjects and in three at-risk individuals below the age of 51. The V family mutation is a conservative amino acid change (E120D) that is found in all four affected individuals and in one at-risk individual in the pedigree under the age of 50 years.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations